Data Rules: Reinventing the Market Economy - Cristina Alaimo; Jannis Kallinikos (The MIT Press, 2024)
A new social science framework for studying the unprecedented social and economic restructuring driven by digital data.Digital data have become the critical frontier where emerging economic practices and organizational forms confront the traditional economic order and its institutions. In Data Rules, Cristina Alaimo and Jannis Kallinikos establish a social science framework for analyzing the unprecedented social and economic restructuring brought about by data. Working at the intersection of information systems and organizational studies, they draw extensively on intellectual currents in sociology, semiotics, cognitive science and technology, and social theory. Making the case for turning "data-making" into an area of inquiry of its own, the authors uncover how data are deeply implicated in rewiring the institutions of the market economy.The authors associate digital data with the decentering of organizations. As they point out, centered systems make sense only when firms (and formal organizations more broadly) can keep the external world at arm's length and maintain a relative operation independence from it. These patterns no longer hold. Data transform the production of goods and services to an endless series of exchanges and interactions that defeat the functional logics of markets and organizations. The diffusion of platforms and ecosystems is indicative of these broader transformations. Rather than viewing data as simply a force of surveillance and control, the authors place the transformative potential of data at the center of an emerging socioeconomic order that restructures society and its institutions.
Keywords: 330; Data; Digital Technology; Platforms; Ecosystems; Value Creation; Digital Innovation; Cognition; Knowledge; Communication